DISEASES CAUSED BY ALCOHOLISM: CAUSES, MEDICAL CONSEQUENCES, AND CARE PROCESSES (International journal of medical sciences, 2026)
This article discusses the dangers of alcohol consumption, the diseases that result from it, proper care approaches, and aims to provide the public with a comprehensive understanding of this harmful habit. It also highlights its social risks and pathological conditions.